Content and essence of independent educational activity of students of high school - Полякова, В. Я. (Pedagogy of Higher and Secondary Education, 2012)
Polyakova V. Yа. Content and essence of independent educational activity of students of high school. The author posits the problem of defining the content and the essence of the notions «high-school pupils’ independent educational activity», «organizing high-school pupils’ independent educational activity», and «self-directed work».